Hydrocracking of Crude Palm Oil over Bimetallic Oxide NiO-CdO/biochar Catalyst - Allwar Allwar; Rina Maulina; Tatang Shabur Julianto; Annisa Ayu Widyaningtyas (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
The bimetallic oxide NiO-CdO/biochar catalyst was prepared by coprecipitation and calcination methods. Characterizations of catalyst were carried out using Fourier Transform Infra Red (FTIR), Surface Area Analyzer (SAA), X-ray Diffraction (XRD), and Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX) mapping methods. The catalyst showed a good average crystalized size of 12.30 nm related to the nanoparticles and high dispersion of Ni and Cd metals  on the biochar surface. Analysis of liquid fuel products was observed using Gas Chromatography - Mass Spectrometry (GC-MS) which was separated to the main product of gasoline fraction (C6–C10), and the second product of kerosene fraction (C11–C16), and diesel fraction (C17–C23). The presence of the catalyst in the hydrocracking resulted in more liquid product of 56.55 wt% than the thermal cracking with a liquid product of 20.55 wt%. The best performance activity of catalyst was found at a temperature of 150 °C with high selectivity to hydrocarbon fuel with 12 types of gasoline fractions (39.24 wt%) compared to gasoline fractions obtained at higher hydrocracking temperatures of 250 °C and 350 °C. The results of this study showed that the bimetallic oxide catalyst supported with biochar from palm kernel shell plays an important role in the hydrocracking process to increase the selectivity of the gasoline fraction. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).